PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP IT DAR EL-IMAN PADANG - Hendrian, Veliantiqa (Departemen Matematika, 2023)
Understanding of mathhematical concept is one of the objective of learning matematics which is expected to be well mastered by students. But in fact, students understanding of matematical concepts is still low. This can also be seen in class VIII IT Dar El-Iman Padang Middle School. One of the effort that can be made to increase students understanding of mathematical concept is to apply the Number Heads Together cooperative learning model. The instrument used was a test of understanding mathematical concepts in the form of essay quations which were analyzed by t-test. Basedd on the results of data analyzed obtained P-value = 0.032, less than α = 0.05, meaning that the understanding of mathematicall concepts of students who learn with the cooperative learning model of the Number Heads Together type is better than the undertanding of mathematical concept of students who learn with direct learningg model in class VIII SMP IT Dar El-Iman Padang.Keywords– Understanding of mathematical concepts, NHT, Direct learning